Neutrophil extracellular traps in urinary tract infection - Krivošíková, Katarína; Šupčíková, Nadja; Gaál Kovalčíková, Alexandra; Janko, Jakub; Pastorek, Michal; Celec, Peter; Podracká, Ľudmila; Tóthová, Ľubomíra (Frontiers in Pediatrics, 2023)
Background: Urinary tract infection (UTI) are common types of bacterial infection in children. UTI treatment is aimed to prevent complications including hypertension, proteinuria, and progression to chronic kidney disease. Activated neutrophils release chromatin-based structures associated with antimicrobial proteins called neutrophil extracellular traps (NETs). We aimed to describe the role of NET-associated markers in children with UTI as well as the role of NETs formation in a mouse model of UTI. Material and Methods: Markers of NETs including extracellular DNA (ecDNA), myeloperoxidase (MPO) and cathelicidin were analyzed in children with febrile UTI caused by E. coli (n=98, aged 0.3 – 1.3 years) and in healthy controls (n=50, 0.5 – 5.2 years). Moreover, an acute experimental model of UTI was performed on PAD4 knock-out mice with diminished NETs formation (n=18), and on wild-type mice (n=15). Results: Children with UTI had significantly higher urinary NETs markers including total ecDNA, nuclear DNA and mitochondrial DNA, altogether with MPO and cathelicidin. The concentrations of MPO and cathelicidin positively correlated with ecDNA (r=0.53, p≤0.001; r=0.56, p≤0.001, respectively) and the number of leukocytes in the urine (r=0.29, p≤0.05; 0.27, p≤0.05, respectively). Moreover, urinary MPO was related to cathelicidin levels (r=0.61, p≤0.001). In the experimental model, bacterial load in the bladder (20-fold) and kidneys (300-fold) was significantly higher in PAD4 knock-out mice than in wild-type mice. Conclusions: Higher urinary NETs makers – ecDNA, MPO and cathelicidin and their correlation with leukocyturia in children with UTI confirmed our hypothesis about the association between NETs and UTI in children. Higher bacterial load in mice with diminished NETs formation suggests that NETs are not only a simple consequence of UTI, but might play a direct role in the prevention of pyelonephritis and other UTI complications.